Pengaruh Pembelajaran IPA dengan Model Problem Based Learning (PBL) Berbantuan Media Komik Digital Terhadap Kemampuan Berpikir Kritis Siswa Kelas V SD - Marisha Herwanti; Endang Widi Winarni; Irwan Koto (UNIB Press, 2024)
This research aims to analyze the influence and relationship of science learning with the PBL model assisted by digital comic media on critical thinking skills in the concluding dimension and further explanation dimension. The type of research used is quasi-experimental research using a pretest-posttest control group design. The type of data used is quantitative and qualitative data using instruments in the form of interviews, question instruments and expert validation sheets. Based on the research results, it was found that the use of the PBL model assisted by digital comic media had a significant effect on the concluding dimensions. This is shown by the posttest average of the concluding dimension in the control class being 72, while the posttest average in the experimental class is 85. The use of the PBL model assisted by digital comic media has a significant effect on the further explanation dimension. This is shown by the average posttest of the concluding dimension in the control class being 75, while the posttest average for the experimental class is 88. Furthermore, there is a relationship between the critical thinking ability of the concluding dimension and further explanation in science learning using the PBL model assisted by digital comic media. This is indicated by a significance value of 0.004 and has a fairly strong relationship with a correlation coefficient of 0.595.